Instrumen Kepuasan Pasien Terhadap Pelayanan Keperawatan : Literature Review - Badrin, Nina Nisrina; Rachmawaty, Rini; Kadar, Kusrini (Jurnal Endurance, 2019)
Patient satisfaction is one of indicator to assess the quality of health services. Measurement of patient satisfaction with nursing services is needed as an evaluation material for nursing management to ensure and improve the quality of nursing services. Several instruments of patient satisfaction with nursing services have been developed. The purpose of this Literature Review is to identify instruments of patient satisfaction with nursing services. This literature review examines the results of development and psychometric testing research of patient satisfaction instruments through article search in PubMed and Google scholar databases with keywords : patient satisfaction, nursing care, instrument, development, tools, psychometric, validity and reliability. We reviewed 20 articles. There are 7 instruments for assessing patient satisfaction with nursing services, namely the questionnaire SERVQUAL, HCAHPS, RPSS, GNCS, NSNS, PSNCQQ and PPHEN. Patient satisfaction instruments consist of several dimensions including individual assessment, communication, staff response, technical competence, interpersonal competence, health education, facilities, hospital environment, comfort, information on return, collaboration and coordination when patients are discharged from the hospital. Based on this literature review it can be concluded that there are several instruments and dimensions that can be used to assess patient satisfaction. But, it is necessary the development of patient satisfaction instruments by involving the perspective of the service provider and incorporating the dimensions of caring as the essence of nursing services. Kepuasan pasien merupakan salah satu indikator untuk menilai kualitas pelayanan kesehatan. Pengukuran  kepuasan pasien terhadap pelayanan keperawatan diperlukan sebagai bahan evaluasi bagi manajemen keperawatan untuk menjamin dan meningkatkan kualitas pelayanan keperawatan. Beberapa instrumen kepuasan pasien terhadap pelayanan keperawatan telah dikembangkan. Tujuan Literature Review ini untuk mengidentifikasi instrumen kepuasan pasien terhadap pelayanan keperawatan. Literature review ini menelaah hasil penelitian pengembangan dan uji psikometrik instrumen kepuasan pasien melalui pencarian artikel di database PubMed dan Google scholar dengan kata kunci : patient satisfaction, nursing care, instrument, development, tool, psychometric, validity dan reliability. Kami melakukan review terhadap 20 artikel. Ada 7 instrumen penilaian kepuasan pasien terhadap pelayanan keperawatan yaitu kuesioner SERVQUAL, HCAHPS, RPSS, GNCS, NSNS, PSNCQQ dan PPHEN. Instrumen kepuasan pasien terdiri dari beberapa dimensi termasuk penilaian individu, komunikasi, tanggapan staf, kompetensi teknis, kompetensi interpersonal, pendidikan kesehatan, fasilitas, lingkungan rumah sakit, kenyamanan, informasi kepulangan, kolaborasi dan koordinasi ketika pasien keluar dari rumah sakit. Berdasarkan literature review ini dapat disimpulkan bahwa untuk menilai kepuasan pasien terhadap terdapat beberapa instrumen dan dimensi yang dapat digunakan. Namun perlu pengembangan instrumen kepuasan pasien dengan melibatkan perspektif dari pemberi pelayanan dan memasukkan dimensi caring sebagai esensi dari pelayanan keperawatan.